A study of practical drawing skills and knowledge transferable skills of children based on STEAM education - Yu, Lan; Li, Yanfang (Frontiers in Psychology, 2022)
The STEAM education involves children's ability to integrate and apply their knowledge of science, technology, engineering, arts, and mathematics. The application and transfer of interdisciplinary knowledge in practical activities is the structure of STEAM education. This study assesses children's practical drawing skills and transferable skills based on the global features of their realistic figure drawing. The drawings incorporate the visual information and the multidisciplinary knowledge that children acquire. The assessment variables of the global features are observation perspectives, baseline, and comparison. The results showed that most children present their works through the front view. The children of different age groups show differences in express baseline and comparison features. Boys and girls show some variances in baseline features. Moreover, children are relatively unskilled at applying interdisciplinary knowledge in their drawings.